Ultrathin Corrugated Metallic Strips for Ultrawideband Surface Wave Trapping at Terahertz Frequencies - Yan Liu; Cizhe Fang; Genquan Han; Yao Shao; Yan Huang; Hongjuan Wang; Yibo Wang; Chunfu Zhang; Yue Hao (IEEE Photonics Journal)
The dispersion properties of the ultrathin spoof slow-wave plasmonic waveguide based on different ultrathin metal strip grooves have been simulated using the finite element method. The dispersion characteristics of the four different surface plasmon polariton (SPP) waves are thoroughly analyzed by the dispersion curves, electric intensity distribution, and power flow distribution. As a conclusion, the gradient arch-shape waveguide has been chosen as an ideal slow-wave system for trapping SPP waves. Furthermore, the reflected location for the SPP waves on the arch-shape corrugated metal strip at different frequencies has been compared by three methods. It is demonstrated that such an ultrathin gradient arch-shape waveguide provides an ultrawideband performance for trapping surface waves, which permits broadband trapping of terahertz radiation.